Teaching Social Justice through Mathematics: A Self-Study of Bridging Theory to Practice - Lisa Harrison (Middle Grades Review, 2015)
In this self-study I critically reflect upon my experience guest teaching a seventh grade unit that integrated social justice and mathematics in an urban school district. As a teacher educator who was newly introduced to the scholarship of social justice mathematics, I analyze my meaning-making process of bridging my conceptual understanding of social justice mathematics to my actual teaching practice to better understand the complexity of addressing issues of social justice and merging them with the content of mathematics. I end this article by discussing the implications for my role as a middle grades teacher educator who wants her majority middle class white preservice teachers to incorporate issues of social justice into their own teaching practices.